A Cognitive Linguistic analysis of HAND and FACE metaphors and metonymies in Jordanian Arabic - Abu Rumman, Ronza; Obeidat, Mohammed; Haider, Ahmad S; Sahari, Yousef (Public Journal of Semiotics, 2024)
This study aims to investigate the metaphorical and metonymical uses of hand and face in Jordanian Arabic (JA) by adopting a version of Conceptual Metaphor Theory (CMT) based on the notion of main meaning focus. A 30,000-word corpus was built for the sake of this study. The original Metaphor Identification Procedure (Pragglejaz Group, 2007) was employed to identify metaphorical expressions; then, Steen’s (2007) procedure was used to extract the conceptual metaphors. The results showed that hand as a source domain can be used to conceptualize character traits, cultural values, states, and emotions, whereas face as a source domain can be used to conceptualize character traits and emotions. This conceptualization is realized through metaphtonymies in which the source domain is constructed metonymically. The findings also showed that there are both similarities and differences between JA and other languages and varieties in relation to hand and face metaphorical conceptualizations. Similarities are attributed to the universality of human embodiment, whereas differences are related to cultural variations. The study recommends that future studies be conducted on the metaphor and metonymies of other body parts, including eye, heart, head, tongue, back, mouth, etc.